Id, Ego, and Superego of the Character Naoko in Haruki Murakami’s Novel Norwegian Wood - Irawati, Farah Rizky; Jumino, Jumino (Sabda: Jurnal Kajian Kebudayaan, 2021)
The paper aims to analyze the main character, Naoko, in Haruki Murakami’s novel Norwegian Wood based on Freud’s theory of id, ego, and superego. The type of data used in this study is qualitative data. The primary source used in this study is the Norwegian Wood novel written by Haruki Murakami. To obtain the data related to support the discussion, the library research and content analysis method is implemented. The data analysis approach used in this study is Freud’s personality theory of the id, ego, and superego. The results of this study indicate that there are forms of id, ego, and superego in Haruki Murakami’s Norwegian Wood novel which are reflected by the character, Naoko. Through the analysis of the id, ego, and superego, the personality, behavior, and internal struggles of Naoko can be explained.